Haydn and the Aesthetics of Naivety. Issue 4 (15th September 2021) - Friedman, Jacob
Abstract: Contending with rapid urbanization in the eighteenth century, some writers advocated a better understanding of mankind in its most 'natural' state. This impulse manifested itself in the arts as an idealization of 'naivety'. Yet this ideal began to fade in the nineteenth century as Romantics prioritized intense expressivity and engagement with raw emotional complexities of life. Naivety came to be seen as an irresponsible retreat from reality. Writers on both sides of this redefinition of naivety positioned Joseph Haydn as the model 'naive' composer. Celebrated in his lifetime for his musical wit, Haydn nonetheless was always closely associated with his unpretentious, rustic origins. This essay contextualizes the fascination with Haydn's supposed naivety within cultural trends at the turn of the nineteenth century and beyond. It demonstrates how changing attitudes towards the aesthetic category of naivety can partly explain the vicissitudes of Haydn's reception history in the eighteenth and nineteenth centuries.